Hubungan Penggunaan Kontrasepsi Hormonal dengan Hasil Pemeriksaan Inspeksi Visual Asam Asetat (IVA) - Novia Arista Cahyani; Adib Ahmad Shammakh; Sabariah Sabariah; Putu Dedi Arjite (Jurnal Health Sains, 2023)
Cervical cancer is a malignancy of cells that occurs in the cervix. In 2015, in NTB there were 8,020 people who had cervical cancer and in 2016 it had increased to 14,431 people. Hormonal contraception is a risk factor for cervical cancer. This study aims to determine the relationship between the use of hormonal contraception and VIA examination results at the Meninting Public Health Center. Cross Sectional research design with medical record measurement tools. A total of 59 research samples were carried out using a purposive sample sampling technique in patients who underwent IVA examinations at the puskesmas, stating that from June 2021 - November 2022 data. Bivariate analysis test using the Chi Square correlation test. The results showed that 30 samples had positive IVA and 29 samples had negative IVA results. Obtained a p-value of 0.011 (p-value,0.05) for the use of contraceptive pills with IVA examination results, a P-value of 0.000 (p-value 0.05) for the use of injecting contraceptives with IVA examination results and a p-value of 0.030 (p- value, 0.05) for the use of implant contraception with IVA examination results. There is a significant relationship between the use of hormonal contraception and the results of visual inspection of acetic acid (IVA) at the Meninting Health Center.